1510 Precarious employment conditions and its association with heart rate variabilityin mexican hospital workers. (24th April 2018) - Martínez, G; Radon, K; Rodriguez, D; Herrera, R; Parra, M
Abstract : Introduction: Psychosocial working conditions such as employment precariousness or an imbalance between effort and reward at the workplace might result in cardiovascular diseases. One marker of cardiovascular effects is Heart Rate Variability (HRV). The objective of this study was to analyse the relation between precarious employment and HRV in health and administrative workers employed at a hospital in Mexico City. Methods: In this cross-sectional study, 206 hospital employees without known cardiovascular diseases participated (response 90%). An interview-based questionnaire assessed sociodemographics, employment conditions, employment precariousness (EPRES) and lifestyle factors. HRV was measured over 10 min in sitting posture. Standard Deviation (SDNN) of the RR intervals over a five minutes was calculated (IBM SPSS 24). Results: Healthcare personnel (n=106) was less likely to be active smokers (9% vs 29%) than administrative workers. Healthcare workers reported lower employment duration (24% vs 7% duration <5 years), working more hours per week (19% vs 7% working ≥60 hours/week), and more shift work (22% vs 11%) than the comparison group. They were more affected by temporality of the contract (27% vs 7%) and were less likely to suffer from economic deprivation (46% vs 69%; all pChi 2 <0.05) than office workers. Mean SDNN did not differ between healthcare workers (49, 93±SD 31, 91) and administrative workers (54, 26±41, 50; pt-Test =0, 33). This was confirmed after adjusting for potential confounders. The only significant work-related predictor of SDNN was shift work (Beta: −16, 68; 95% CI: −30, 69 to −2, 67). Discussion: Although Mexican healthcare professionals frequently suffer from precarious employment conditions, shift work was the main predictor for lower HRV in our study population.